A perfect blood ebook With bonus material. - Harrison, Kim (The Hollows, 2012)
Ritually murdered corpses are appearing across Cincinnati, terrifying amalgams of human and other. Pulled in by the FIB to help investigate, former witch-turned-day-walking demon Rachel Morgan soon realizes a horrifying truth: others want to create their own demons, and to do so they need her blood. She's faced vampires, witches, werewolves, demons, and more—but this time Rachel's toughest challenge might be humanity itself.